An Extended Approach to Quantify Triacylglycerol in Microalgae by Characteristic Fatty Acids - Yang, Miao; Fan, Yan; Wu, Pei-Chun; Chu, Ya-Dong; Shen, Pei-Li; Xue, Song; Chi, Zhan-You (Frontiers in Plant Science, 2017)
Microalgae represent a third generation biofuel feedstock due to their high triacylglycerol (TAG) content under adverse environmental conditions. Microalgal TAG resides in a single cell and serves as a lipid class mixed with complicated compositions. We previously showed that TAG possessed characteristic fatty acids (CFAs) for quantification and was linearly correlated with the relative abundance of CFA within certain limits in microalgae. Here, we defined the application range of the linear correlation between TAG and CFA in the oleaginous microalgae Chlamydomonas reinhardtii and Phaeodactylum tricornutum. In addition, TAG quantification was further expanded to a wide range of levels and the absolute amounts of saturated or monounsaturated CFAs, 16:0 and 18:1n9 of C. reinhardtii and 16:0 and 16:1n7 of P. tricornutum, instead of polyunsaturated CFAs, were verified to be linearly correlated to TAG levels throughout the entire period of nitrogen stress. This approach utilizes a single fatty acid to quantify TAG mixtures, and is rapid, simple and precise, which provides a useful tool for monitoring TAG accumulation of distinct microalgal species and facilitating high-throughput mutant screening for microalgae.